2002
DOI: 10.1253/circj.66.557
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prognosis of Patients With Mildly Dilated Cardiomyopathy.

Abstract: eft ventricular (LV) dilatation and systolic dysfunction are the hallmarks of idiopathic dilated cardiomyopathy (DCM). 1 Although the degree of LV dilatation is generally thought to be one of the predictors of poor outcome, 2-5 several investigators have reported that the prognosis of patients with mild LV dilatation (MDCM) is variable. [6][7][8] However, the long-term prognosis and changes in the echocardiographic parameters of such patients are unknown and so we aimed to elucidate the long-term prognosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…Thus, patients with lesser degrees of NIDCM were not included. Finally, the presence of diabetes8 10 and left atrial dilatation17 23 have also been previously reported by more than one study, but in both cases, we did not observe any differences in this population. Whether this has to do with the preselected nature of this population, or just a small sample size is not known.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, patients with lesser degrees of NIDCM were not included. Finally, the presence of diabetes8 10 and left atrial dilatation17 23 have also been previously reported by more than one study, but in both cases, we did not observe any differences in this population. Whether this has to do with the preselected nature of this population, or just a small sample size is not known.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, a wide spectrum of LV size was observed among patients with nonischemic HF, with a substantial proportion (24%) having either normal sex‐specific LVEDV or mild LV dilation. Such a high prevalence of patients with mildly dilated cardiomyopathy is remarkably similar to that reported in previous small single‐center studies, suggesting that it could be an intrinsic characteristic of about one quarter of patients with nonischemic HF 3,4 . Whether mild LV dilation depends on specific biologic characteristics of the disease is as yet unknown.…”
Section: Discussionsupporting
confidence: 84%
“…It has been known since the 1980s that patients with heart failure (HF) as a result of dilated cardiomyopathy may present with end‐stage HF despite having only mild left ventricular (LV) dilation 1–4 . The clinical and prognostic significance of this finding was found to vary.…”
mentioning
confidence: 99%
“…cations, whereas the other group shows definite impairment of hemodynamics together with left atrial dilation despite modest LV dilatation, and these patients have a poorer prognosis and must be carefully followed. 23) In the current study, the prognosis of patients with non-dilated LV size was significantly poorer than that of patients with dilated LV size despite similar baseline characteristics and treatment during follow-up, although some D-HCM patients with small LV size might be in an early phase of D-HCM with large LV size. The reason for these results is not clear, but we speculate that patients with non-dilated LV size have greater LV stiffness, leading to restricted LV dilatation and more elevated LV end-diastolic pressure.…”
Section: Discussionmentioning
confidence: 47%
“…12,19) On the other hand, several investigators have reported that the prognosis of DCM patients with mild LV dilatation is variable and that end-stage heart failure occurs in a subgroup of patients with DCM despite mild LV dilatation. [20][21][22][23] We previously reported that DCM patients with mild LV dilatation have two important features: one group of patients with early and mild DCM may stabilize or improve through the natural course or with appropriate medi- 71.0 ± 20.6 (n = 5) 64.5 ± 20.6 (n = 15) 0.546 E/Ea septal 12.0 ± 3.3 (n = 2) 15.9 ± 7.0 (n = 7) 0.479 Laboratory data BNP, pg/mL 700.1 ± 532.5 (n = 3) 328.5 ± 307.1 (n = 10) 0.144 Creatinine, mg/dL 1.03 ± 0.49 (n = 3) 0.93 ± 0.16 (n = 10) 0.753 Sodium, mmol/L 140.7 ± 3.2 (n = 3) 139.9 ± 2.5 (n = 11) 0.667 Total bilirubin, mg/dL 1.30 ± 1.13 (n = 2) 0.72 ± 0.22 (n = 11) 0.599…”
Section: Discussionmentioning
confidence: 99%